Social Theory for Quantum Times - Hanna-Kaisa Hoppania (Journal of Social Ontology, 2024)
Discourse theories and methods have been a staple in social and political studies for a long time. However, even in the most advanced accounts of post-structuralist ontology and epistemology within the social sciences, materiality is somewhat under-theorized, weakening discursive approaches and leading to a sense that social and material/natural worlds are in some significant way separate and operate differently. In this paper Karen Barad’s theory of agential realism, which builds on quantum physics, is deployed to show that this need not be the case. The paper explores the question of materiality and matter and its relation to discourse, by bringing Barad’s insight and a strand of post-structuralist discourse theory together. I argue that Barad’s agential realism can account for how matter matters also in post-structuralist social science, by discussing the similarities of the two approaches and how they work together.  The article contributes to the discussion on new materialism, the question of agency and structure and to the onto-epistemology of social sciences and the concept of matter.